Surface morphology and thermogravimetric analysis of polyaniline (PANI) incorporated cotton fabric - Parvez, Md. Shohan; Rahman, Md Mustafizur; Mahendran, Samykano; Ali, Mohammad Yeakub (Tech Science Press, 2023)
With the exponential development in wearable electronics, a significant paradigm shift is observed from rigid electronics to flexible wearable devices. Polyaniline (PANI) is considered as a dominant material in this sector, as it is endowed with the optical properties of both metal and semiconductors. However, its widespread application got delineated because of its irregular rigid form, level of conductivity, and precise choice of solvents. Incorporating PANI in textile materials can generate promising functionality for wearable applications. This research work employed a straightforward in-situ chemical oxidative polymerization to synthesize PANI on Cotton fabric surfaces with varying dopant (HCl) concentrations. Pre-treatment using NaOH is implemented to improve the conductivity of the fabric surface by increasing the monomer absorption. This research explores the morphological and structural analysis employing SEM, FTIR and EDX. The surface resistivity was measured using a digital multimeter, and thermal stability is measured using TGA. Upon successful polymerization, a homogenous coating layer is observed. It is revealed that the simple pre-treatment technique significantly reduces the surface resistivity of Cotton fabric to 1.27 kΩ/cm with increasing acid concentration and thermal stability. The electro-thermal energy can also reach up to 38.2°C within 50 s with a deployed voltage of 15 V. The modified fabric is anticipated to be used in thermal regulation, supercapacitor, sensor, UV shielding, antimicrobial and other prospective functional applications.